Studi Pendahuluan Penggunaan Katalis Logam-HAp Pada Pembuatan Biodiesel - Syafruddin Syafruddin; Yelmida Azis; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The safety and sustainability of an energy source, along with biodegradability is a parameter whether an alternative energy considered successful or not. Currently, biodiesel is an environmentally friendly and has low manufacturing cost. Biodiesel cathegorized as fatty acid methyl esther (FAME) which is generated from fat or oil. In this research, palm fatty acid destillate (PFAD) is used as raw material to produce biodiesel. PFAD is converted into FAME through single stage estherification. This estherification reaction combine 25 gram of PFAD with 97 gram of methanol with mixing rate of 350 rpm at 60˚C for 1, 2, and 3 hours. 0,25 gram of metal-hydroxyapatite catalyst (Cu-HAp, Co-HAp, Ni-HAp, dan HAp) will assist in the process of converting PFAD into FAME. The focus of this study is the effect of time and type of metal-HAp on the conversion of PFAD into FAME. The highest yield of biodiesel is acquired at the usage of (3%) Cu-HAp catalyst for 3 hours. Physical test result has fulfilled SNI 04-7182-2006 which includes 0.84 g/ml density, 4.8 cSt viscosity, 120 ˚C flash point, 61.48% yield, acid number of 0.73 mg KOH/gr oil. Based on the GC-MS (Gas Chromatography-Mass Spectrometer) analysis, the main component of the PFAD-based biodiesel is 53.1% hexadecanoic methyl esther, 32.81% 9-octadecanoic methyl esther and 5,93% 9,12-octadecadinoic methyl esther.Keywords: Biodiesel, Estherification-transestherification, Methanol, Metal-HAp catalysts, PFAD